2014
DOI: 10.1177/0954405414522796
|View full text |Cite
|
Sign up to set email alerts
|

Tool wear mechanisms in machining of three titanium alloys with increasing β-phase fraction

Abstract: Mechanical and microstructural properties of titanium alloys change with β-phase fraction. This in turn influences the dominant tool wear mechanisms in their machining. This work therefore involves turning experimentation on three titanium alloys with varying β-phase fraction, namely, α, α+ β and β-rich alloys using coated carbide tools, to identify dominant wear mechanisms, which hitherto have not been adequately investigated. The dominant wear mechanisms were investigated using scanning electron microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The change in grain structure from a to b structure also causes changes in mechanical properties, chip formation and tool wear mechanism. 10 Micromachining of such materials is thus a more complicated science than simple scaling down of tool-workpiece dimensions, as the micro-tool transits between a and b grains that leads to more complicated tool dynamics and wear mechanisms that are essentially different from conventional/macro-machining. Very little research on mechanical micromachining of titanium alloys has been reported as compared with other materials.…”
Section: Introductionmentioning
confidence: 99%
“…The change in grain structure from a to b structure also causes changes in mechanical properties, chip formation and tool wear mechanism. 10 Micromachining of such materials is thus a more complicated science than simple scaling down of tool-workpiece dimensions, as the micro-tool transits between a and b grains that leads to more complicated tool dynamics and wear mechanisms that are essentially different from conventional/macro-machining. Very little research on mechanical micromachining of titanium alloys has been reported as compared with other materials.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of varying fraction of β-phase in titanium alloys was experimentally investigated on the tool wear characteristics of a turning process. 34 Abrasion, abrasion with built-up edge, and plastic deformation of cutting edge were found to be the main tool damage mechanisms in α, α + β, and β-rich alloy, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…15 Abrasion with built-up edge and plastic deformation of the cutting edge are found to be dominant in the machining of titanium alloys with different β fractions. 16,17 Although studies on the tool-wear behaviour in machining are as old as metal cutting, 18,19 one of the earliest efforts to quantify tool life is attributed to the tool life equation by FW Taylor 20 and its modified versions, which relates the tool life with machining parameters. A number of analytical models are proposed by researchers for the tool-wear prediction in different cutting applications and tool–workpiece combinations.…”
Section: Introductionmentioning
confidence: 99%